Business ethics searches: A socioeconomic and demographic analysis of U.S. Google Trends in the context of the 2008 financial crisis. (23rd January 2017) - Faugère, Christophe; Gergaud, Olivier
Abstract: A socioeconomic and demographic analysis of U.S. Google Trends for queries about Business Ethics and Greed is proposed in the context of the 2008 financial crisis. The framework is grounded in the ethical decision‐making literature. Two models using micro and macro‐type variables are tested using GLM and GEE regression techniques. The frequency of these Google queries varies positively with the ratio of females, educational attainment, younger adult age, some measures of economic hardship or inequalities, and the lesser the weight of the finance industry represented in each State. The frequency of queries intensifies for these same socioeconomic and demographic categories, in the aftermath of the financial crisis. This article is the first to study the salience of business ethics as an issue in the empirical literature using a nationwide database. It also provides a first empirical study in the specialized literature on "ethics in a time of crisis". This study lays a preliminary groundwork to identify pro‐ethical reform segments of the population, with practical use for financial regulatory agencies.